Brain Gym Video Model for Improving the Beginning Writing Abilities of the Autistic Students - Ary Puspita Ningrum; Abdul Huda; Henry Praherdhiono (Department of Special Education, 2018)
Language is a very necessary thing, especially in writing the beginning. Beginning the writing requires a fine motor ability wich adequate. The fine motor in the students with an intellectual disability is impaired so requiring movement that can coordinate motoric. Brain gym is a simple movement that can be used to train cognitive, motor and flexibility the small muscles of the fingers and coordinates the brain with the shoulders, arms, and eyes. The purpose of this research is to produce brain gymnastics. This video is packaged in CD format which is expected to help students to write the beginning. The research and development method that used in this research was adapted from the Borg & Gall model. The results showed that the brain gym was feasible and effective was applied for the intellectual disability after validation by media experts, brain gym experts, and learning experts, as well as pretest and post-test. Utilization suggestions of this research are: (1) for students: students should pay attention to teacher’s movement and instruction, (2) for the teacher: pay attention to student’s difficulty in moving, especially hand moving.